Age but not BMI Predicts Accelerated Progression of KOA: Data from the Osteoarthritis Initiative - Kyle D. Wallace; Ramzi W. Nahhas; Andrew W. Froehle; Naila Khalil (Ohio Journal of Public Health, 2018)
Background/Objectives: Knee osteoarthritis (KOA) accounts for about 35% of the arthritis burden among adults. Most adults with KOA have slowly-progressing, common knee osteoarthritis (CKOA); however, some individuals experience accelerated KOA (AKOA), rapid progression to end-stage disease within 48 months. This study analyzed individuals without radiographic evidence of KOA at baseline to determine which (baseline) characteristics were associated with progression to CKOA and/or AKOA status 48 months later. Methods: Data (n = 1,561) from the Osteoarthritis Initiative (OAI) were utilized. Multinomial logistic regression was employed to determine the magnitude of association between baseline risk factors and 48-month KOA status (AKOA and CKOA, compared to no KOA). Results: Older age (p = 0.032), greater baseline BMI (p < 0.001), female gender (p = 0.009), and greater baseline PASE score (p = 0.036) were significantly associated with CKOA (11.9% of participants) and/or AKOA (3.5% of participants) at 48 months. Age, BMI, and PASE were all more strongly associated with greater risk of AKOA compared to risk of CKOA (Age: OR = 1.59 vs. 0.97; BMI: OR = 1.62 vs. 1.28; PASE: OR = 1.21 vs. 1.08). Of these, only BMI was significantly associated with greater risk of both AKOA and CKOA. Conclusion: Certain factors impact the risk of AKOA and CKOA differently. Age did not increase the risk of CKOA, but among those with CKOA or AKOA, the proportion with AKOA increased with age. Thus, older age at onset is associated with more rapid KOA progression.
Keywords: Age; osteoarthritis; accelerated knee osteoarthritis; common knee osteoarthritis